2022
DOI: 10.3389/fneph.2022.933954
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Gastrointestinal Complaints in Kidney Transplant Recipients Using Tacrolimus With and Without Mycophenolate Mofetil: A Randomized Controlled Study

Abstract: BackgroundTacrolimus (TAC) combined with mycophenolate mofetil (MMF) is the immunosuppressive regimen in the majority of solid organ transplant recipients. Gastrointestinal complaints are frequent, which is considered predominantly a side effect of MMF. However, systematic research in this field is lacking. The aim of this study is to systematically investigate the burden of gastrointestinal complaints in TAC-treated kidney transplant recipients with and without MMF.MethodsIn a single-center, open-label, rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition, with an average tacrolimus trough level of 6 ng/L the graft function remained stable, no DSA developed and adherence to the once daily immunosuppressive regimen in the TACmono group was significantly better than in the TAC/MMF group (23). Another benefit TACmono recipients experienced, was improvement in diarrhea complaints after discontinuing MMF, as assessed with standardized questionnaires on gastro-intestinal symptoms (24). The benefits of TACmono in terms of less adverse events is of course difficult to quantify in a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with an average tacrolimus trough level of 6 ng/L the graft function remained stable, no DSA developed and adherence to the once daily immunosuppressive regimen in the TACmono group was significantly better than in the TAC/MMF group (23). Another benefit TACmono recipients experienced, was improvement in diarrhea complaints after discontinuing MMF, as assessed with standardized questionnaires on gastro-intestinal symptoms (24). The benefits of TACmono in terms of less adverse events is of course difficult to quantify in a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…MMF has replaced azathioprine in current immune suppressive regimens. MMF use may cause serious gastrointestinal side effects and severely lower the antibody response to vaccination, e.g., COVID-19 vaccines ( 111 113 ). In general, the use of MMF is associated with more infections, particularly viral infections, but it does not seem to increase the risk for cancer significantly and may even have therapeutic potential as an anticancer drug ( 114 116 ).…”
Section: The Intensity Of Maintenance Immune Suppression Regimens—bal...mentioning
confidence: 99%
“…An RCT based on this concept was recently published with 5-year follow-up data and indeed showed that this may be a feasible approach as the results showed no development of DSA, no increased rejection rate, significantly fewer infections, and a much better serological response after COVID vaccination ( 112 , 146 ). Tacrolimus was given as a once-daily formulation, increasing medication adherence, and there were fewer gastrointestinal symptoms after MMF discontinuation ( 83 , 113 , 147 ). Of note, the mean age of the recipients in this trial was 59 years, and recipients with a TCMR treated with T cell-depleting therapy were excluded from randomization.…”
Section: Managing Maintenance Immune Suppression Regimens In Relation...mentioning
confidence: 99%